2018
DOI: 10.1007/s00216-018-0948-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid recognition of volatile organic compounds with colorimetric sensor arrays for lung cancer screening

Abstract: Volatile organic compounds (VOCs) in breath can be used as biomarkers to identify early stages of lung cancer. Herein, we report a disposable colorimetric array that has been constructed from diverse chemo-responsive colorants. Distinguishable difference maps were plotted within 4 min for specifically targeted VOCs. Through the consideration of various chemical interactions with VOCs, the arrays successfully discriminate between 20 different volatile organic compounds in breath that are related to lung cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Handa et al (72) investigated the breath samples of 50 patients with LC and 39 healthy controls by IMS and revealed that this method had a sensitivity of 81.3% and specificity of 89.7%. Nonetheless, sensors and IMS are limited in terms of detection and, thus, are usually coupled with complex algorithms (72)(73)(74). The advantages and disadvantages of nucleic acid-based (75-78), protein-based (79) and cell-based (80,81) detections were compared with VOC-based detection as displayed in Table I.…”
Section: Emerging Non-invasive Detection Methods For Lcmentioning
confidence: 99%
“…Handa et al (72) investigated the breath samples of 50 patients with LC and 39 healthy controls by IMS and revealed that this method had a sensitivity of 81.3% and specificity of 89.7%. Nonetheless, sensors and IMS are limited in terms of detection and, thus, are usually coupled with complex algorithms (72)(73)(74). The advantages and disadvantages of nucleic acid-based (75-78), protein-based (79) and cell-based (80,81) detections were compared with VOC-based detection as displayed in Table I.…”
Section: Emerging Non-invasive Detection Methods For Lcmentioning
confidence: 99%
“…Concerning cross-reactive sensing systems, there are five possible categories to which an indicator may belong to: pH responsive, (Brønsted acidity/basicity); metal-ion-containing dyes (Lewis basicity—electron pair donation); redox-responsive metal salts; nucleophilic indicators (responsive to electrophilic analytes) and dyes with large permanent dipoles (e.g., solvatochromic dyes) [ 6 ]. Such optical sensors have been extensively investigated in the field of breath analysis, mainly for LC diagnosis, using both synthetic [ 140 , 193 ] and real-world breath samples [ 127 , 194 ]. Hou et al have achieved to discriminate at first 4 ( Table 2 ) [ 140 ] and then 20 [ 193 ] LC-related VOCs in two separate studies, with accuracies of 100% and 90%, respectively.…”
Section: Types Of Nanomaterial-based Sensors In Breath Analysismentioning
confidence: 99%
“…Such optical sensors have been extensively investigated in the field of breath analysis, mainly for LC diagnosis, using both synthetic [ 140 , 193 ] and real-world breath samples [ 127 , 194 ]. Hou et al have achieved to discriminate at first 4 ( Table 2 ) [ 140 ] and then 20 [ 193 ] LC-related VOCs in two separate studies, with accuracies of 100% and 90%, respectively. Mazzone et al achieved to differentiate LC patients and HC, with moderate accuracies [ 127 , 194 ], as well as LC patients of different histologies with a higher accuracy percentage ( Table 2 ) [ 127 ].…”
Section: Types Of Nanomaterial-based Sensors In Breath Analysismentioning
confidence: 99%
“…Colorimetric gas sensors can provide highly selective and discriminatory responses towards mixtures of various VOCs; hence, they are normally employed in e-noses for the detection of multiple odors and compounds [ 44 ]. Similar to interferometric devices, sensitivities of colorimetric gas sensors are generally at a few ppm and detection limits can be down to hundreds of ppb.…”
Section: Gas Sensors For Vocs Detectionmentioning
confidence: 99%